Estrategia sostenible para mejorar la eficiencia de los servicios de inseminación artificial en ganado bovino en el trópico - Pedroso Sosa, Rodolfo (2024)
The aim of this study was to evaluate the efficiency of artificial insemination (AI) services in Holstein x Brahman cows under a heat induction programme. Three experiments were carried out. In Exp. 1, a retrospective analysis of the efficiency of AI insemination of 41 000 cows treated with the combination of progesterone and oestradiol benzoate or equine chorionic gonadotropin (eCG) was carried out. In Exp. 2 it was evaluated 863 cows inseminated after heat induced with progesterone and oestradiol benzoate to know the physiological events that occur before and after service in herds with a high incidence of anoestrus. Gynaecological examinations and determination of progesterone in milk were performed. The purpose of Exp. 3 was to improve the effectiveness of AI services for cows in postpartum anoestrus treated with progesterone and oestradiol benzoate combined with a technique to identify and induce the return to service of females that did not conceive. Only 30% of the cows exceeded 40% conception. The best results were obtained when using eCG (47% vs 29%). The problems associated with the low conception rate were unfertilized oestrus, embryonic mortality and anoestrus after breeding (Exp. 2). The return to service induction technique increased (p<0.001) the conception rate of the second induced service and the percentage of accumulated pregnancy in the treated group compared to the control (69.0 and 32.0%, respectively) (Exp. 3).